Caracteristici ale vieţii sociale în Republica Moldova - Mocanu, Victor; Mocanu, Ion (Calitatea Vieții, 2009)
This paper is dedicated to the study of the interdependence of the economic, political, and social processes in the Republic of Moldavia, studying also the influence of socio-demographic and personal characteristics on the formation of social and political orientations of the population. The article is based upon the results of a scientific study conducted by The Moldavian Sociologists and Demographists Association, in September 2008, on a representative national selection (1 586 questionnaires applied to respondents in 88 towns and villages, the error margin bellow 2,6%). The paper is dedicated to the ways of functioning of radical market transformations and of the development of the democratic process. The authors have gathered important empirical data about the social context which was created in the former soviet states, after the collapse of the USSR.